Evaluation of ram sperm quality post-thawing by using two energy sources and two cryoprotectants - Ruiz G., Luis (2015)
The aim of this study was to evaluate the effect of two monosaccharides (fructose and glucose) and two cryoprotectants (glycerol and ethylene glycol) on semen quality after the cryopreservation process under a 2 x 2 factorial arrangement. The variables evaluated were progressive motility, viability, and acrosomal integrity. Motility was greater with the use of glycerol (65.5%) compared to the use of ethylene glycol (49.0%) (p<0.05); also, motility using fructose was higher with the use of fructose (59.3%) than when using glucose (55.1%) (p<0.05). Acrosomal integrity was superior with the use of glycerol (58.2%) compared with ethylene glycol (42.0%); also, acrosomal integrity was superior with the use of fructose (53.8%) than when using glucose (46.4%) (p<0.05). The energy source x cryoprotectant interaction was not statistically significant. The results showed that the use of glycerol as a cryoprotectant and fructose as an energy source more effectively prevent loss of semen quality during cryopreservation in comparison to ethylene glycol and glucose, respectively.